2013
DOI: 10.1016/j.econedurev.2013.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Do vouchers lead to sorting under random private school selection? Evidence from the Milwaukee voucher program

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…These are public schools that provide families with another schooling option free of tuition payments. Chakrabarti (2013) shows that the decisions of low-income families to enroll their children in a private school are very sensitive to modest costs such as paying for transportation, even when the schools charge no tuition. We know of only one study that examines the causal impact of greater charter school availability on private school enrollment rates.…”
mentioning
confidence: 99%
“…These are public schools that provide families with another schooling option free of tuition payments. Chakrabarti (2013) shows that the decisions of low-income families to enroll their children in a private school are very sensitive to modest costs such as paying for transportation, even when the schools charge no tuition. We know of only one study that examines the causal impact of greater charter school availability on private school enrollment rates.…”
mentioning
confidence: 99%
“…Studies from other states also revealed equivalent results on sorting. These studies found that voucher students have relatively higher initial achievement than their public-school peers who are also eligible for vouchers (Chakrabarti, 2013;Epple et al, 2004;Howell, 2004;McEwan, 2000). As a result, the long-lasting negative effect of the competition in public schools for the last five years of ICSP appears to result from a worsening learning environment (Epple et al, 2004;Epple & Romano, 1998), owed to the departure of relatively high achieving students.…”
Section: Discussionmentioning
confidence: 99%
“…Voucher users are more likely to have attended private schools before being offered a voucher, begging the question of whether they are subsidizing the status quo, instead of increasing social mobility (Belfield 2006; Paul, Legan, and Metcalf 2007). Further, admission procedures at schools accepting vouchers can lead to increased sorting by both income and ability (Chakrabarti 2013). Voucher recipients are disproportionately Euro-American or Hispanic, with African Americans underrepresented (Metcalf et al 2002).…”
Section: Assignment Policy Tools To Address Inequalitymentioning
confidence: 99%